2018
DOI: 10.1155/2018/8720169
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photoluminescence in Gold Nanoparticles Doped Homogeneous Planar Nematic Liquid Crystals

Abstract: This study reported the photoluminescence (PL) of gold nanoparticles (GNPs) doped planar nematic liquid crystals (NLCs) and observed around 64% enhancement in PL intensity with suitable doping amounts of GNPs in liquid crystals 5CB. The enhancement in PL intensity has been attributed to the increased surface area from GNPs, which results in increased emissions due to the increased scattering of excitation. The subsequent decay of PL intensity with doping more amounts of GNPs in liquid crystals 5CB was due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Nematic LC 4-cyano-4 -pentylbiphenyl (5CB) is well studied mesogen. The effects of dispersion of TiO 2 NPs [3,4], CuS NPs [8], GNPs (gold) [46,47], and BaTiO 3 NPs [48] on the ionic behavior and screening effect, alignment and electro-optical properties, photoluminescence, and thermodynamic, optical and electrical properties have been studied extensively. In these works, different issues have been addressed.…”
Section: Dispersion Of Nanoparticles In Nematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nematic LC 4-cyano-4 -pentylbiphenyl (5CB) is well studied mesogen. The effects of dispersion of TiO 2 NPs [3,4], CuS NPs [8], GNPs (gold) [46,47], and BaTiO 3 NPs [48] on the ionic behavior and screening effect, alignment and electro-optical properties, photoluminescence, and thermodynamic, optical and electrical properties have been studied extensively. In these works, different issues have been addressed.…”
Section: Dispersion Of Nanoparticles In Nematicsmentioning
confidence: 99%
“…The NRs can be organized at the nanoscale either as individual NPs or as chain-like self-assembled nanostructures. Chang et al [47] investigated the photoluminescence (PL) in the GNPs dispersed homogeneous planar nematic 5CB. With a suitable amount of NPs dispersion around 64% increase in PL intensity was observed, which may be due to the increased surface area from GNPs.…”
Section: Dispersion Of Nanoparticles In Nematicsmentioning
confidence: 99%
“…The enormous influence of nanomaterials on modern technology is solely due to their size-dependent electronic, optical, magnetic, and chemical properties. Because of their potential scientific and technological relevance, investigation into micro/nano-scale colloids dispersed in liquid crystals (LCs) has stimulated enormous interest within this framework. The best examples of anisotropic fluids are LCs, which have proven to be an appropriate medium for studying the interaction between colloidal particles and LCs. A few theoretical and experimental studies on colloidal particles dispersed in LCs have been conducted, with the shape/size of colloids and the self-assembling nature of the LCs being heavily considered. ,− …”
Section: Introductionmentioning
confidence: 99%
“…The surface features (such as surface imperfections) and dispersion stability of colloidal GNPs have a strong influence on their fluorescence emission. The luminescence increase is aided by establishing effective surface passivation technologies and screening suitable surface ligands. For example, Chang et al reported 64% increase in photoluminescence (PL) intensity in liquid crystals 5CB after doping appropriate amounts of GNPs. Biradar and co-workers reported a detailed study on GNP-dispersed deformed helix ferroelectric liquid crystals (DHFLCs) which clearly showed sevenfold and ninefold enhancement in the PL intensity with 20 and 100 μL of GNP solution.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Au nanoparticles have been used as a dopant to NLCs from the cyanobiphenyls homologous series (nCB). Depending on the homolog of the defect-free layers, increases in the dielectric anisotropy ∆ε, the optical anisotropy ∆n, elastic constant K, viscosity γ, and broadening of the N phase were found [29][30][31][32][33]. The modifications of the material parameters were explained as a results of creating clusters of two different types: (a) nanoparticle clusters with LC molecules (for smaller concentrations) and (b) nanoparticle clusters among themselves (for higher concentrations) [34].…”
Section: Introductionmentioning
confidence: 99%